2020
DOI: 10.1002/smtd.202000491
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Hepatic Transporters as Multimodal Gene Reporters for Cell‐Based Medicine

Abstract: Hepatic transporters facilitate the uptake of xenobiotic compounds and confer immense potential as multimodality reporters, as they can uptake multitude of bioluminescent, fluorescence, near Infra-red (NIR), and magnetic resonance imaging (MRI) compounds. Here, it is aimed to identify the prospects of three human hepatocyte membrane proteins, organic anion transporters (OATP) 1B1, OATP1B3, and sodium-taurocholate cotransporting polypeptide in tracing the transplanted cells dynamics, by the uptake of clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…By eliminating multiple steps required of conventional uptake transporter assays, our approach saves time, enables higher throughput, and would in principle reduce stepwise error accumulation. Our data is consistent with an understanding that D‐luciferin is a substrate for OATP1B1 and ‐1B3 (16, 17), TMQ derivatization blocks its activity with luciferase but does not generally prevent uptake, that free D‐luciferin is rapidly released from TMQ in the intracellular compartment of living cells, and it can be detected in a luciferin‐luciferase reaction (14). The latter two points made it necessary to design probes with negligible transporter‐independent uptake.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…By eliminating multiple steps required of conventional uptake transporter assays, our approach saves time, enables higher throughput, and would in principle reduce stepwise error accumulation. Our data is consistent with an understanding that D‐luciferin is a substrate for OATP1B1 and ‐1B3 (16, 17), TMQ derivatization blocks its activity with luciferase but does not generally prevent uptake, that free D‐luciferin is rapidly released from TMQ in the intracellular compartment of living cells, and it can be detected in a luciferin‐luciferase reaction (14). The latter two points made it necessary to design probes with negligible transporter‐independent uptake.…”
Section: Discussionsupporting
confidence: 88%
“…The objective of the present study was to develop no-wash addonly assays for detecting inhibitors or substrates acting as competitive inhibitors of OATP1B1 and -1B3 transport activity, and in this way enable a higher throughput approach. The assays would rely on derivatives of the OATP substrate D-luciferin (16,17). To confirm that human OATP1B1 and -1B3 transport D-luciferin and establish a model system for testing luciferin derivatives as uptake probes, we applied D-luciferin to human embryonal kidney cells (HEK293) with or without ectopic overexpression of recombinant human OATP1B1 or -1B3 (OATP1B1, OATP1B3 or Control cells).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most of the other studies have assembled or encapsulated MRI contrast agents and ICG into drug carriers, aiming to achieve multimodal imaging capabilities. 67,93–102 Fan et al self-assembled Fe 3+ and DOX molecules to synthesize a bioactive metal–organic framework (bio-MOF), and then wrapped another structure consisting of Gd 3+ and 1,3,5-benzenetricarboxylic acid (H 3 BTC) on the surface of the Fe-DOX nanoparticles, and then adsorbed ICG to form a Fe-DOX@Gd-MOF-ICG nanoplatform. 102,103 This nanoplatform enables combined MR/PA/PT multimodal imaging-guided chemotherapy, and photothermal and photodynamic therapy.…”
Section: Amphiphilic Properties Obtained By Combining Hydrophilic And...mentioning
confidence: 99%
“…Recently, a couple of studies indicated that the organic anion-transporting polypeptides (OATP) family proteins could mediate the uptake of ICG, thereby achieving near-infrared (NIR) fluorescence imaging. [17][18][19] Because of its clinical availability and deep tissue imaging capabilities, these OATP protein are considered as the potential reporter gene system with multiple biomedical applications.…”
Section: Introductionmentioning
confidence: 99%